South Indian Customs - Ayyar, P. V. Jagadisa (Gurugram Shubhi Publications, 2025)
South Indian customs refer to the cultural region typically covering the South Indian states of Tamil Nadu, Karnataka, Kerala, Andhra Pradesh, and Telangana. The idea of South India is closely linked to the Dravidian ethnic and linguistic identity and therefore it can also refer to groups in central India, such as the Gondi and the Kui. Similar to India it is difficult to define a common essence of South Indian culture. That being some common threads include the eternal universe through the celebration of the beauty of the body and femininity. It is exemplified through its dance, clothing, and sculptures
Keywords: South Indian Culture